AN EXAMINATION OF LANGUAGE REQUIREMENTS FOR NEWLY-GRADUATED STUDENTS BY QUANTITATIVE RESEARCH - Robert Sandor Szucs; Zoltan Mate; Eva Laszlo; Kata Foldi; Stefan Mommertz (European Scientific Journal, ESJ, 2014)
Nowadays the rising unemployment rate for newly-graduated students poses a considerable problem. Although obtaining a degree and certificate are not enough on the labour market, it is a fact that college graduates' unemployment rates over all are still lower than the national average. These days the successful graduate job applicant has to (fluently) speak foreign language(s). In order to ensure that candidates can fulfil this requirement, universities and colleges have to modify the language teaching strategy according to the needs of the labour market.